2014
DOI: 10.1371/journal.pone.0109233
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dark Septate Endophytic Fungal Isolates in the Accumulation of Cesium by Chinese Cabbage and Tomato Plants under Contaminated Environments

Abstract: Following the 2011 Fukushima Daiichi Nuclear Power Plant accident, the preservation of the food chain from radionuclides contamination has become of crucial importance. The potential of Dark septate endophytic fungi in the management of Cs accumulation in plants under contaminated environments was investigated using Chinese cabbage and tomato plants. Four endophytic fungal isolates of different species, i.e. Pseudosigmoidea ibarakiensis I.4-2-1, Veronaeopsis simplex Y34, Helminthosporium velutinum 41-1, and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 37 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…This suggests that E. pisciphila , found colonizing numerous plant roots in an ancient Pb-/Zn- Slag heap in China 21 and previously reported as a fish-pathogenic fungus 22 23 , confers a marked cadmium tolerance to its host plant and plays a functional role as a beneficial plant-associated fungus with DSE morphological characteristics. The reduced Cd accumulation in both shoots and roots of DSE-inoculated maize suggests that plants which accumulate and/or tolerate Cd have evolved an alternative mechanism, utilizing DSE colonization, to resist taking up metals in the soil and/or to tolerate metals inside cells 14 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that E. pisciphila , found colonizing numerous plant roots in an ancient Pb-/Zn- Slag heap in China 21 and previously reported as a fish-pathogenic fungus 22 23 , confers a marked cadmium tolerance to its host plant and plays a functional role as a beneficial plant-associated fungus with DSE morphological characteristics. The reduced Cd accumulation in both shoots and roots of DSE-inoculated maize suggests that plants which accumulate and/or tolerate Cd have evolved an alternative mechanism, utilizing DSE colonization, to resist taking up metals in the soil and/or to tolerate metals inside cells 14 19 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, field surveys from Ban, et al 18 showed that DSE colonization was negatively correlated with the translocation of Pb (r = −0.88, p < 0.05) accumulated in six dominant plant species grown on Qiandongshan Pb-Zn mine tailings, China. To evaluate the role of DSEs in phytoremediation of radioactive cesium (Cs), Diene, et al 19 identified the distinct responses of DSE-inoculation on Cs accumulation in two commercial crops; they observed that DSEs significantly decreased Cs accumulation in DSE-inoculated tomato but enhanced phytoremediation of Cs by Chinese cabbage, while also significantly increasing the biomass of both crops by up to 82 and 122% (for Chinese cabbage and tomato, respectively), compared to non-inoculated controls. Also, data from Likar and Regvar 14 revealed that DSEs isolated from Salix caprea reduced metal uptake and improved the general physiology of their host plants via various effects, such as increasing chlorophyll concentrations and transpiration rates, for example.…”
mentioning
confidence: 99%
“…Various factors have been investigated and suggested as positive regulators of cesium accumulation in plants. For example, inoculation with root-associated microorganisms has been shown to improve cesium accumulation in plants 13 14 15 16 . Some researchers have reported that an arbuscular mycorrhizal (AM) fungi improve cesium phytoaccumulation efficiency 17 18 , while others have contradicted this 19 20 , and there is an ongoing debate on the effect of cesium on colonisation of AM fungi 21 .…”
mentioning
confidence: 99%
“…Solanaceous plants have a high affinity for DSE fungi. The highest number of DSE fungal isolates have frequently been obtained from roots of solanaceous plants (Diene et al 2014). For example, Narisawa et al (2007) showed that eggplant was a particularly effective species for baiting the DSE fungus Heteroconium chaetospira from the soil.…”
Section: Discussionmentioning
confidence: 99%